Are bullying behaviors tolerated in some cultures? Evidence for a curvilinear relationship between workplace bullying and job satisfaction among Italian workers - Giorgi, G. (2015)
Since the early 1990s, increasing attention has been paid to the impact of workplace bullying on employees’ well-being and job attitudes. However, the relationship between workplace bullying and job satisfaction remains unclear. This study aims to shed light on the nature of the bullying-job satisfaction relationship in the Italian context (n = 1,393 employees from different organizations). As expected, the results revealed a U-shape curvilinear relationship between workplace bullying and job satisfaction after controlling for demographic variables. In contrast to the curvilinear model, the results support a negative linear relationship between workplace bullying and psychological well-being, in which higher exposure to negative acts at work is associated with diminished well-being. In addition, gender and job position significantly predicted mental health scores where men and managers reported a better psychological well-being than women, blue-collar, and white-collar employees. Practical and theoretical implications are discussed according to these results.